(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2019)
The language learning strategies has emerged as a new field of research in the language pedagogy. In the last forty years there have been lot of debate over defining, classifying and developing a theoretical framework for the language learning strategies (LLS). This also seems true because there has been a paradigm shift in the role of the learners who are now seen as active collaborators in the knowledge creation. In the present paper, the researcher would like to investigate the role of these LLS in learning Spanish as foreign language in India. The researcher would provide a initial description of definitions, concept development and its historical trajectory. The paper will also talk about the difference and similarities between communication strategies and learning strategies. The seminal work of Rubin started a new debate in this field of LLS and the research in this field has attracted the attention of many well researchers such as Ellis and Oxford. Other pioneering researchers who have contributed to this field are O‘Malley and Chamat, Nunan and Cohen. The paper will also throw light on some of the important language learning strategies employed by the Indian students and will examine critically a typical Indian classroom and also gives example of some of his research findings related to learning Spanish as foreign language in Indian universities.